2019
DOI: 10.3389/fpsyt.2019.00782
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Self-Reported Psychotic Experiences, Clinically Relevant Psychotic Experiences, and Attenuated Psychotic Symptoms in the General Population

Abstract: Purpose: Psychotic experiences in childhood (such as hearing voices or being suspicious) represent an important phenotype for early intervention. However, these experiences can be defined in several ways: self-reported psychotic experiences (SRPE) rely exclusively on the child’s report, clinically validated psychotic experiences (CRPE) are based on clinical assessment, and attenuated psychotic symptoms (APS) represents a categorization to do with clinical relevance in relation to severity. Very few studies hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 62 publications
(94 reference statements)
1
13
0
1
Order By: Relevance
“…This recommendation is also relevant for current operationalisations of at-risk syndromes, which require formulating a differential diagnosis between psychosis risk and other psychopathological dimensions such as the SIPS or the DSM-5-APS 2 . Although psychotic experiences are frequent in the general population 103 , 104 , clinical attenuated psychotic symptoms are infrequent and not normally distributed. Only 0.3% of the general young population meet DSM-5-APS criteria 2 , 105 .…”
Section: Discussionmentioning
confidence: 99%
“…This recommendation is also relevant for current operationalisations of at-risk syndromes, which require formulating a differential diagnosis between psychosis risk and other psychopathological dimensions such as the SIPS or the DSM-5-APS 2 . Although psychotic experiences are frequent in the general population 103 , 104 , clinical attenuated psychotic symptoms are infrequent and not normally distributed. Only 0.3% of the general young population meet DSM-5-APS criteria 2 , 105 .…”
Section: Discussionmentioning
confidence: 99%
“… 9 PLEs are considered a dimensional, 10 transdiagnostic marker of psychopathology 11 , 12 that is not necessarily specific to psychosis risk, as only a subset of these children is at risk for conversion to psychotic disorders 13 or other psychiatric disorders in adulthood. 14 Notably, research indicates that self-reported PLEs, even those not confirmed with clinical interview, are still clinically relevant and associated with higher rates of psychopathology 15–17 and reduced functioning. 17 , 18 Several large cross-sectional datasets over the past 2 decades have examined the correlates of PLEs, finding associations with racial/ethnic minority status, 19 internalizing symptoms, 20–22 externalizing symptoms, 20 developmental impairments, 23 and cognitive impairments, 23 , 24 including reading, 25 working memory, 26 , 27 and processing speed 28 impairments.…”
Section: Introductionmentioning
confidence: 99%
“…As respostas a alguns itens do IPO-Br demandam maior autorreflexão e clareza acerca das emoções experimentadas e do modo como a pessoa vê a si mesma. Falhas nessa capacidade autorreflexiva, juntamente com prejuízos no julgamento, podem gerar escores em um instrumento de autorrelato que não representam adequadamente o paciente 25 . Ainda, ocorre o fato de a OP borderline ser amplamente estudada enquanto existem pouquíssimos estudos sobre a OP psicótica na perspectiva da teoria psicodinâmica das relações de objeto, resultando em lacunas no conhecimento e aprofundamento do funcionamento estrutural psicótico 26 .…”
Section: Discussionunclassified